Cannabidiol Treatment for Lennox-Gastaut Syndrome at a Single Tertiary Center in South Korea - Han Na Jang; Min-Jee Kim; Mi-Sun Yum; Tae-Sung Ko (Korean Child Neurology Society, 2023)
Purpose This study evaluated the efficacy and tolerability of cannabidiol (CBD) as an add-on therapy for childhood-onset Lennox-Gastaut syndrome (LGS). Methods This retrospective study enrolled patients who visited the Department of Pediatric Neurology at Asan Medical Center from March 2019 to February 2022 and were treated with CBD. Electronic medical records and clinically relevant factors (including the type of epilepsy and seizures, etiology, and the number of concomitantly used anti-epileptic drugs) were reviewed. The outcome was clinical response to CBD (≥50% or <50% seizure reduction at 1, 3, and 6 months after CBD introduction and the last follow-up visit). Relevant adverse events were monitored. Results Thirty patients were included. The median age of epilepsy onset was 5.5 years (interquartile range [IQR], 3.3 to 25.3), with a median treatment duration of CBD of 6 months (IQR, 3.3 to 7.0). Sixteen patients (53.3%) showed ≥50% seizure reduction at the last follow-up. In a univariate analysis, patients whose epilepsy commenced after 3 years of age were more likely to respond to CBD (odds ratio, 10.11; 95% confidence interval, 1.05 to 97.00; P=0.04). Adverse events were observed in 11 patients (36.6%); the most common adverse event was somnolence. Conclusion CBD could be a treatment option for children and young adults with drug-resistant LGS with a tolerable safety profile. Age at epilepsy onset (>3 years) was associated with a favorable response to CBD treatment. Further prospective studies with larger populations are needed to evaluate the tolerability and efficacy of CBD in patients with drug-resistant epilepsy of various etiologies.